Overexpression of B11 Gene in Transgenic Rice Increased Tolerance to Aluminum Stress - Devi Media Siska; . Hamim; . Miftahudin (HAYATI Journal of Biosciences, 2017)
Rice cultivation on acid soils is mainly constrained by aluminum (Al) toxicity. However, rice has tolerance mechanism to Al stress, which is controlled by many genes. B11 gene is one of the Al- tolerance gene candidate isolated from rice var. Hawara Bunar. It has not been known whether overexpression of the gene in Al-sensitive rice is able to increase Al tolerance. The research objective was to analyze root morphological and physiological responses of transgenic rice overexpressing B11 gene to Al stress. The experiment was carried out using five rice genotypes including two varieties (Hawara Bunar and IR64) and three T4 generation of transgenic lines, that are T8-2-4, T8-12-5, and T8-15-41. All rice genotypes were grown in nutrient solution for 24 h (adaptation period), and then were exposed to 15 ppm Al for 72 h (treatment period) and recovered in normal nutrient solution for 48 h (recovery period). The result showed that the overexpression of the B11 gene in T8-2-4, T8-12-5, and T8-15-41 transgenic lines improved tolerance to Al stress based on root growth characters, accumulation of Al, root cell membrane lipid peroxidation, and root tip cell structure.